A Thousand Blunders: The Grand Trunk Pacific Railway and Northern British Columbia - Roy, Patricia E. (Labour / Le Travail, 1998)
The article reviews the book, "A Thousand Blunders: The Grand Trunk Pacific Railway and Northern British Columbia," by Frank Leonard.